Dealing with supply disruptions on the european natural gas market: Infrastructure investments or coordinated policies? - Jan Abrell; Léo Chavaz; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2019)
Natural gas plays an important role in many European energy systems especially with regard to the envisioned transition towards a less carbon intensive energy supply. Being dependent on imports - especially from Russia - this raises questions about the future development and security of Europe's gas supply. Using a numerical network model of the European gas system we assess 1) the potential impact of infrastructure extensions for Europe's gas supply and 2) the role of supply security policies in coping with a disruption of Russian imports via the Ukraine. Our results indicate that overall the European gas infrastructure is sufficient for average market conditions. Due to the strong dependency on Russian imports, however, disruptions during the winter months could lead to load curtailment. Projected network extension (Southern Gas Corridor, Nord Stream 2, and new LNG terminals) or a strategic storage policy coordinated across Europe has the potential to reduce this shortage. The positive impact of an extended network, however, also depends on the capability of the global gas market to provide flexible gas that can be reallocated towards Europe. The majority of demand curtailment can already by countered by a relatively modest amount of strategic storage (20% to 30%) if their use during crisis situations is coordination across European countries.
Keywords: 330; Europe; natural gas; North Stream; network model; storage; supply security